Assessment of Long-Term Changes in Knowledge and Attitudes of Household Contacts of COVID-19 Cases in Northern Spain - Noelia Vera-Punzano; Vanessa Bullón-Vela; Carme Miret; Jéssica Pardos-Plaza; Manuel García Cenoz; Pere Godoy; Jesús Castilla; Àngela Domínguez; Diana Toledo; Iván Martínez-Baz (Infectious Disease Reports, 2024)
This study aims to describe the long-term changes in the knowledge of, and attitudes towards, COVID-19 and its preventive measures in northern Spain. A telephonic survey was performed among household contacts of COVID-19 cases in Catalonia and Navarre between May 2022 and December 2023. Knowledge and attitudes were assessed through 12 questions using a Likert scale, and responses were grouped as correct or incorrect. The change from baseline to the 6-month follow-up was evaluated with the absolute difference (AD) using the proportion of correct answers. At baseline, 299 subjects were contacted, of whom 63.2% (189) completed the 6-month follow-up. Correct knowledge of transmission (>85%) and the use of preventive measures (>92%) were observed at baseline and maintained over time. The attitudes towards face mask use remained adequate over the course of six months (>79%). However, attitudes regarding the use of face masks indoors (AD = −16.4%; p < 0.001) and those who thought that COVID-19 had a negative impact on their lives (AD = −16.5%; p < 0.001) decreased after 6 months. In the post-acute phase of the pandemic, household contacts maintained the correct level of knowledge towards COVID-19, while some attitudes decreased. These results should serve as a guide for health policy makers in decision-making in case of a new increase in the incidence of SARS-CoV-2.